Marketing and its application in music in professional training in the higher education system - Nurmoldayev, Serik; Nussipzhanova, Bibigul; Begembetova, Galiya (Pedagogy and Psychology, 2021)
This article discusses the issues of the essence of marketing and marketing activities, their features in the non-profit service sector, namely in a higher musical educational institution. The marketing activity of modern institutions of music education has been studied. The experience of marketing activities in musical education institutions is summarized. The necessary and sufficient formal and substantial characteristics of marketing activities have been identified. In addition, the authors made a bias towards the features of educational services that form the features of music marketing in this area - the main emphasis here is on the quality of interaction between an educational institution, on the one hand, as well as consumers and customers - students, future potential employers, government governing structures, on the other hand. In the field of music education, marketing is becoming a vehicle through which music or art educational institutions communicate and promote their goals, values ​​and products to students, their employees and society at large. Marketing is closely related to managing the relationship between producers and consumers of services. In education, marketing is concerned with managing the relationship between teachers and students.